Split-current magnetoresistor - Phetchakul, Toempong; Taisettavatkul, Prateep; Yamwong, Wittawat; Poyai, Amporn (My University, 2013)
The split-current magnetoresistor is proposed here. The structure likes the series magnetoresistor that one end split into two symmetrical terminals, so it is the magnetoresistor with three terminals. It uses the Hall effect current mode as magnetoresistor but the output is the differential current instead of resistance. It shows good linearity and can detect the magnetic field direction. The sensitivity in the differential current of width 100 μm and length 200 μm at 1 mA is 2.788×10-6 A/T constantly while the conventional one in the differential resistance is varied with magnetic field. It is made of silicon non magnetic material so it is compatible with the modern low-voltage current-mode integrated circuit. © (2013) Trans Tech Publications, Switzerland.
Keywords: Current mode; Hall effect; Magnetic resistor; TCAD